Patriarchal Deconstruction in the song “Sit Still Look Pretty” by Daya - Ahmad Taufiq; Ashadi Ashadi; Yeni Artanti (Journal of Language and Literature, 2025)
Music plays a key role in shaping culture, reflecting societal norms, and serving as a tool for critique. This study examines how Sit Still, Look Pretty by Daya challenges traditional gender roles using Derrida’s deconstruction theory, which questions binary oppositions and redefines female autonomy. By analyzing the song’s lyrics and themes, this research explores how popular music can dismantle patriarchal norms and provide a more inclusive understanding of gender and identity. Using a qualitative approach and Derrida’s concepts of différance and binary opposition, the study reveals how the song critiques societal expectations that prioritize women’s physical appearance and passive roles, while emphasizing ambition and independence. Key findings include themes such as: 1) women and appearances, 2) women and identity, 3) women and self-sufficiency, 4) women and materialism, 5) women and control, 6) women and ambition, 7) women and gender expectations, and 8) patriarchy. The song goes beyond rejecting traditional norms; it reconstructs a framework of female identity centered on agency and empowerment. By destabilizing binary oppositions like active/passive and dominant/submissive, the song challenges listeners to engage with entrenched societal values critically. It highlights the importance of breaking free from patriarchal systems that perpetuate gender inequality and reimagines a world where women can define their roles and ambitions without societal constraints. This analysis demonstrates the potential of popular music as a transformative tool for deconstructing oppressive ideologies and fostering more inclusive identities.